Dietary Self-Monitoring Related to Appropriate Weight Gain in Pregnancy. (29th May 2020) - Horton, Sarah; Herman, Amy; Hull, Holly; Hand, Lauren
Abstract: Objectives: The purpose of this study was to assess the relationship between dietary self-monitoring and adherence to gestational weight gain (GWG) guidelines in women randomized to a 12-week high fiber (HF) diet (≥30 g/day). These relationships were also evaluated within maternal pre-pregnancy BMI groups. Methods: Twenty pregnant women were enrolled, and 12 were randomized and completed the intervention. The intervention group only tracked their daily diet for a total of 82-days. Women met weekly with a registered dietitian via telephone for group lessons on consuming a HF diet. Participants tracked dietary intake with a mobile application (LifeScience Technologies AtHome). For these analyses, a day was considered tracked if any food item was entered. Participants could only see fiber grams; all other nutrition data were hidden. GWG was classified as excessive or not-excessive based on 2009 IOM guidelines. ANOVA was used to detect a difference in days tracked between excessive and not-excessive gainers. Within BMI groups, linear regression determined the relationship between days tracked and GWG and dietary intake. Results: Out of 82 days, women tracked a mean of 68.8 ± 22.8 days. No difference in days tracked was found between excessive ( n  = 5) and non-excessive ( n  = 7) weight gainers (57.0 ± 32.4 vs. 77.1 ± 7.2 days, respectively; P  = 0.14). The number of days tracked was related to GWG during the intervention (R 2  = 0.44; P  = 0.03). In overweight/obese women ( n  = 5), tracking was related to GWG (R 2  = 0.92; P  = 0.04), however, no relationship was found in normal weight women ( n  = 7; P  = 0.18). The number of days tracked was not related to calorie or fiber intake. Conclusions: Dietary self-monitoring was related to better gestational weight control throughout the 82-day intervention, but not dietary measures. Larger studies are needed to expand these findings and to determine the possible mechanism by which self-monitoring improves gestational weight outcomes. Funding Sources: This study was supported by an NIH Clinical and Translational Science Award.